Web Based Correspondence Application as an Effort to Improve Public Service in Wonosari Village: Aplikasi Surat Menyurat Berbasis Web Sebagai Upaya Untuk Meningkatkan Pelayanan Publik Desa Wonosari - Findawati, Yulian; Rosid, Muhammad Alfan; Hindarto; maulana, Metatia intan (Universitas Muhammadiyah Sidoarjo, 2022)
The role of digital transformation facilitates bureaucratic services in the village. Current technological developments bring many changes to various aspects, including the aspect of public administration services, one of which is online correspondence services which are useful for improving the village government management system so that it can work efficiently and effectively. So far, in Wonosari Village, correspondence services such as birth certificates, certificates of good behavior, transfer certificates and other letters are still done manually so it takes a long time. Therefore, a Web-based Correspondence Application was built in Wonosari Village. Where in this application consists of a menu of master data, Master Letters, Reporting, Validation of Letters and user settings. This application is built using the PHP programming language and MYSQL database. With this Web-based correspondence application, it is hoped that it will simplify and speed up the correspondence administration process at the village government level.